(untitled) (Student’s Journal of Health Research Africa, 2023)
Introduction The goal of the current investigation was to assess the relationship between the occurrence of coronary artery disease (CAD) and the neutrophil-to-lymphocyte ratio (NLR). Additionally, we wanted to provide an appropriate NLR cut-off for the diagnosis of CAD. Methods A total of 124 individuals underwent coronary angiography, and they were split into two groups: category 1 (people without coronary artery disease) and category 2 (those with coronary artery disease). Results The findings revealed a statistically significant positive correlation (p< 0.05) between heightened concentrations of WBC, neutrophils, monocytes, NLR, hs-CRP, CPK-MB, and troponin I with the presence of the disease. Based on the findings of subcategory analysis, it was observed that the association exhibited a greater degree of significance (p< 0.04) within the male demographic and among individuals of advanced age. Of all the markers evaluated, the NLR exhibited the most robust predictive capacity for CAD, as indicated by the highest odds ratio of 1.395 (95% CI: 0.941–2.360; p = 0.04). The determined optimal cut-off value for the diagnosis of CAD was found to be 2.12 (p< 0.001), based on the NLR. The current investigation additionally identified a correlation between the NLR and other biochemical indicators, specifically hs-CRP, CPK-MB, and troponin I, utilizing quartile analysis. Conclusion The NLR is a straightforward diagnostic indicator that has demonstrated efficacy in the identification of CAD within the Indian population. A defined threshold of 2.12 has been established for optimal diagnostic accuracy. Recommendations The utilization of NLR, owing to its cost-effectiveness and convenient accessibility, can be utilized as an initial screening modality, particularly in smaller healthcare facilities, to assess the need for employing more expensive and time-consuming imaging techniques in the diagnosis of coronary artery disease.